2020
DOI: 10.1111/1751-7915.13731
|View full text |Cite
|
Sign up to set email alerts
|

Polyploid engineering by increasing mutant gene dosage in yeasts

Abstract: The yeast Saccharomyces cerevisiae, widely used for ethanol production, is one of the best-understood biological systems. Diploid strains of S. cerevisiae are preferred for industrial use due to the better fermentation efficiency, in terms of vitality and endurance as compared to those of haploid strains. Whole-genome duplications is known to promote adaptive mutations in microorganisms, and allelic variations considerably contribute to the product composition in ethanol fermentation. Although fermentation can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In the previous report (Fukuda et al, 2021), we indicated that the phenotypic change induced by 1 copy of the partial dominant mutation in the FAS2 gene obviously declined as yeast ploidy increased. For quantitative evaluation of the genetic dominance of the LEU4 G516S mutation, in the current study, dose-response curves for TFL were compared among strains with a hetero allelic mutation LEU4 G516S .…”
Section: Resultsmentioning
confidence: 75%
“…In the previous report (Fukuda et al, 2021), we indicated that the phenotypic change induced by 1 copy of the partial dominant mutation in the FAS2 gene obviously declined as yeast ploidy increased. For quantitative evaluation of the genetic dominance of the LEU4 G516S mutation, in the current study, dose-response curves for TFL were compared among strains with a hetero allelic mutation LEU4 G516S .…”
Section: Resultsmentioning
confidence: 75%
“…Karyotyping: The extraction of genomic DNA and karyotyping was performed according to the previous study [8,9]. DNA was extracted using the alkali extraction method.…”
Section: Methodsmentioning
confidence: 99%
“…However, some brewery Fermentation 2022, 8, 62 2 of 12 yeasts have three chromosomes and are called aneuploids [5,6]. Aneuploidy yeast cells have physiologies that are different from euploidy yeast cells [7,8]. Recently, we first showed that the chromosomal aneuploidy of brewery yeasts alters brewery profiles [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is especially common in industrial strains where it is thought to be a result of adaptation to industrial conditions, fermentation target products or by-products [200]. Aneuploidy can be a result of a strain's adaptation to different drugs and confer drug resistance that has perspectives in biotechnological engineering [202,203]. At the same time aneuploidy may lead to a decrease in viability, apparently due to the imbalance of multiple proteins and the increased burden on protein quality control systems [204][205][206].…”
Section: Generation Of Aneuploid Strainsmentioning
confidence: 99%